The Role of Academic Burnout, Resilience, and Perceived Stress in Predicting Students\\\' Addiction Potential - mojtaba salmabadi; Hossein Salimi Bajestani; hamze Khayami Abiz; Reza javan (Drug Control Headquarters, Research and Education Office, 2015)
Objective: This study aimed at determining the role of academic burnout, resilience, and perceived stress in predicting students' addiction potential. Method: In this correlational study, the number of 200 high school students in of South Khorasan province was selected as the participants through random cluster sampling and they responded to the three pertinent questionnaires, namely resilience scale, academic burnout scale, perceived stress scale, and addiction potential scale. Results: The results showed that academic burnout, perceived stress, and resilience were positively correlated with addiction potential. Similarly, there was a significant positive relationship between academic burnout and perceived stress. Conclusion: Dimensions of burnout (emotional exhaustion, apathy, impotency), dimensions of perceived stress (negative emotional responses and coping ability level), and resilience could predict 20% of addiction potential. Among these dimensions, only coping ability level and resilience were significantly effective in predicting addiction potential therefore, educational authorities are recommended to pay more attention to the prevention and treatment of addiction in students towards having a healthy society.